2013
DOI: 10.1016/j.celrep.2013.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Independent Activation of XBP1s and/or ATF6 Reveals Three Functionally Diverse ER Proteostasis Environments

Abstract: Summary The unfolded protein response (UPR) maintains endoplasmic reticulum (ER) proteostasis through the activation of transcription factors such as XBP1s and ATF6. The functional consequences of these transcription factors for ER proteostasis remain poorly defined. Here, we describe methodology that enables orthogonal, small-molecule-mediated activation of the UPR-associated transcription factors XBP1s and/or ATF6 in the same cell independent of stress. We employ transcriptomics and quantitative proteomics t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

46
727
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 476 publications
(778 citation statements)
references
References 57 publications
46
727
3
2
Order By: Relevance
“…Reduced FT ALLC secretion induced by XBP1s or ATF6 activation was dependent on transcription factor activity, as no reduction in FT ALLC secretion was observed in TMP-or Dox-treated HEK293 DYG cells-a control cell line stably expressing DHFR-YFP and Dox-inducible GFP (Fig. S4B) (40).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reduced FT ALLC secretion induced by XBP1s or ATF6 activation was dependent on transcription factor activity, as no reduction in FT ALLC secretion was observed in TMP-or Dox-treated HEK293 DYG cells-a control cell line stably expressing DHFR-YFP and Dox-inducible GFP (Fig. S4B) (40).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has indicated that remodeling of ER proteostasis pathways selectively influences the secretion of destabilized protein variants relative to more stable protein variants (13,40,41). Thus, Tg-dependent UPR activation could selectively decrease the secretion of destabilized ALLC through the transcriptional remodeling of the ER proteostasis network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 The cytosolic portion of ATF6 contains the bZIP transcriptional activator domain, and after cleavage, this ATF6 fragment migrates to the nucleus to transcriptionally up-regulate ER chaperones and ERAD components, thereby enhancing ER proteinfolding capacity and efficiency of ERAD. 10,12,18,20 Interestingly, ATF6 also transcriptionally up-regulates Xbp1, thereby facilitating IRE1 signal transduction by increasing levels of IRE1's RNase substrate, Xbp1 mRNA. 21 Put together, these initial transcriptional and translational effects of IRE1, PERK, and ATF6 signaling help cells adapt to ER stress by enhancing the fidelity of protein folding, increasing the degradation of damaged/misfolded proteins, and suppressing new protein synthesis.…”
mentioning
confidence: 99%